Curcumin mitigates axonal injury and neuronal cell apoptosis through the PERK/Nrf2 signaling pathway following diffuse axonal injury. Issue 8 (23rd May 2018) - Huang, Tingqin; Zhao, Junjie; Guo, Dan; Pang, Honggang; Zhao, Yonglin; Song, Jinning
Abstract : Diffuse axonal injury (DAI) accounts for more than 50% of all traumatic brain injury. In response to the mechanical damage associated with DAI, the abnormal proteins produced in the neurons and axons, namely, β-APP and p-tau, induce endoplasmic reticulum (ER) stress. Curcumin, a major component extracted from the rhizome of Curcuma longa, has shown potent anti-inflammatory, antioxidant, anti-infection, and antitumor activity in previous studies. Moreover, curcumin is an activator of nuclear factor-erythroid 2-related factor 2 (Nrf2) and promotes its nuclear translocation. In this study, we evaluated the therapeutic potential of curcumin for the treatment of DAI and investigated the mechanisms underlying the protective effects of curcumin against neural cell death and axonal injury after DAI. Rats subjected to a model of DAI by head rotational acceleration were treated with vehicle or curcumin to evaluate the effect of curcumin on neuronal and axonal injury. We observed that curcumin (20 mg/kg intraperitoneal) administered 1 h after DAI induction alleviated the aggregation of p-tau and β-APP in neurons, reduced ER-stress-related cell apoptosis, and ameliorated neurological deficits. Further investigation showed that the protective effect of curcumin in DAI was mediated by the PERK/Nrf2 pathway. Curcumin promoted PERK phosphorylation, and then Nrf2 dissociated from Keap1 and was translocated to the nucleus, which activated ATF4, an important bZIP transcription factor that maintains intracellular homeostasis, but inhibited the CHOP, a hallmark of ER stress and ER-associated programmed cell death. In summary, we demonstrate for the first time that curcumin confers protection against abnormal proteins and neuronal apoptosis after DAI, that the process is mediated by strengthening of the unfolded protein response to overcome ER stress, and that the protective effect of curcumin against DAI is dependent on the activation of Nrf2.